Bridging dialects: translating Aboriginal English into Indonesian in the Novel My Place - Sartika, Delita; Hidayati, Hidayati; Armiwati, Armiwati (UNIB Press, 2025)
This paper examines the translation of non-standard orthographic features of the Australian Aboriginal English (AAE) dialect in Sally Morgan’s biographical novel My Place into the Indonesian language. Addressing the challenges posed by linguistic and cultural untranslatability, this study explores three key questions: (1) What strategies are employed by the translator to convey the AAE dialect into Indonesian? (2) How do these strategies influence the transfer of the original message? (3) What alternative strategies could mitigate linguistic and cultural loss, especially given the sociolinguistic gap between AAE and Indonesian? Following J. K. Chamber’s (2004) features of vernacular universals, the analysis identifies four primary types of non-standard orthographic features of AAE in My Place: (1) Alveolar Substitution in –ing Ending Verbs, (2) Deletion of Initial Unstressed Syllable, (3) Eye Dialect, and (4) Morpheme Simplification. Findings indicate that the translation often fails to retain AAE as a distinctive literary dialect, which is largely due to the absence of equivalents in Indonesian language. The translator predominantly uses standard Indonesian renderings, which reduces the portrayal of non-standard elements of the source text However, the study emphasizes compensation as a practical strategy to minimize translation loss. By compensating for the loss of non-standard effects through other means, such as using elements of a local dialect from the target culture in the translation, translators can maintain the centrality of dialect within the story. Although the exact level of non-standardness may not be fully replicated, this approach preserves some of the cultural and linguistic uniqueness, offering a balanced compromise that conveys the broader essence of AAE dialect in the target text.